Three new species of Eutheiini (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2013)
Three new species of the ant-like stone beetle tribe Eutheiini are described from the People's Republic of China: Eutheia laolongiana sp. n. (Gansu), Veraphis gansuanus sp. n. (Gansu) and V. assingi sp. n. (Sichuan). Key morphological char-acters of the new taxa are illustrated and a distinctly sub-Himalayan distribution of all Eutheiini hitherto known to occur in China is summarized.